DESIGN OF A PROTOTYPE OF PAPER MONEY DETECTOR FOR THE VIEW (JESII: Journal of Elektronik Sistem InformasI, 2023)
To access resources and information, use the library. The issue is that some libraries do not yet have a web-based online system for locating learning resources. Due to their inability to recognize and see money, blind persons are more likely to swap, misappropriate, or even defraud money during buying and selling operations. Designing a "Prototype of Banknote Nominal Detector for Blind People" and creating a "Prototype of Information System Data Presentation of Banknote Detector for Blind People" are the main goals of this study. This system's design adheres to the agile software development process. The rupiah money can be identified by the prototype of the nominal banknote detector based on the nominal entered; the accuracy value is 93% for banknotes in neat conditions, 87% in wrinkled conditions, 71% in wet conditions, and 53% in faded color conditions. And the development of a data presentation system in the form of a dashboard can help admins in managing data from testing activities more easily, and so that data can be stored more systematically.